Al-Ḥīlah al-Shar'iyyah as a Method in Responding to Prayer Problems in Space - Siti Marhamah; Mahsun Mahsun (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
This paper describes the prayer problem for Muslim astronauts in space and provides solutions using the al-ḥīlah al-shar'iyyah method. This paper is qualitative with descriptive-analytic research methods with data sourced from the literature. This paper finds that with the al-ḥīlah al-shar'iyyah method, Muslim astronauts can still carry out their obligations as a mukallaf. They get rukhṣah (dispensation), both related to the direction of the qibla and the determination of prayer times. Rukhṣah, as a result of the al-ḥīlah al-shar'iyyah method, helps Muslim astronauts in two conditions at once, first, in their position as scientists who carry out scientific missions. Second, in his position as a Muslim with his obligations to carry out the sharī'ah.